Bone Health in Osteosarcoma at Presentation and Its Impact on Cancer Treatment: A Case Series of 3 Pediatric Patients. Issue 3 (27th April 2022) - Malcolmson, Caroline; Lautatzis, Maria-Elena; Malkiel, Sarah; Lenherr-Taube, Nina; Traubici, Jeffery; Gupta, Abha; Hopyan, Sevan; Sochett, Etienne; Grant, Ronald
Abstract : Osteosarcoma is the most common pediatric malignant bone tumor. Concomitant osteoporosis has typically been attributed to oncologic therapy. The present case series is aimed to describe 3 patients who presented with osteoporosis or osteopenia before, or early in, their oncology treatment. In our patients, bone health and its complications had significant impacts including pain, reduced mobility, prolonged admission, and delays in recovery. Our patients experienced improvement with resection of their primary tumor and with bisphosphonate infusion. Future studies are required to determine the prevalence osteoporosis at presentation of osteosarcoma and the role of bisphosphonates.